2004
DOI: 10.1021/jf035366k
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of p-Coumaric and Gallic Acids in Rats after Oral Administration

Abstract: Ferulic acid (FA) and p-coumaric acid (CA) are absorbed by the monocarboxylic acid transporter (MCT) in Caco-2 cells, although gallic acid (GA) is not. Therefore, the MCT is selective for certain phenolic acids. Absorption of orally administered CA and GA in rats was studied to obtain serum pharmacokinetic profiles and to investigate their intestinal absorption characteristics in vivo. Rats were administered 100 micromol/kg body weight of CA and GA, and blood was collected from the portal vein and abdominal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
141
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(160 citation statements)
references
References 28 publications
15
141
0
1
Order By: Relevance
“…For example, hydrolysable tannins are degraded to gallic acid, pyrogallol, phloroglucinol, and finally to acetate and butyrate via sequential enzymatic action (29). In particular, oral administration of gallic acid led to intestinal absorption over a period of ϳ60 min in rodents (69), which equated to 76 min in humans (70). Flavonoids including gallate have also been shown to cross into the brain in rodents (68,71,72).…”
Section: Discussionmentioning
confidence: 99%
“…For example, hydrolysable tannins are degraded to gallic acid, pyrogallol, phloroglucinol, and finally to acetate and butyrate via sequential enzymatic action (29). In particular, oral administration of gallic acid led to intestinal absorption over a period of ϳ60 min in rodents (69), which equated to 76 min in humans (70). Flavonoids including gallate have also been shown to cross into the brain in rodents (68,71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, phenolic acids can be absorbed through the intestine by an active transport system whereupon they can prevent oxidative stress (18,19). In addition, compounds containing one or more aromatic hydroxyl groups replace α-tocopherol as a chain-breaking anti-oxidant and restore reduced glutathione as a protective agent in cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…As we expected alphatocopherol at low concentration could significantly prevent the LDL oxidation and delay the lag phase for about 267 min. Protective effect of alpha-tocopherol against copper-induced oxidation of LDL has been shown previously (Konishi, Hitomi, & Yoshioka, 2004). It has been revealed that alpha-tocopherol could have such an inhibitory effect through acting as a scavenger for the chain-carrying lipid peroxyl radicals and thus terminating the lipid peroxidation (Zhang, Chen, Yang, Chen, & Ying, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…However, there is possibility of absorption of some of polyphenolic compounds in gastrointestinal tract without any metallization. For instance, gallic and ellagic acids that have been mentioned as effective antioxidants in pomegranate juice can be directly absorbed by intestinal tract and increase the corresponding circulation levels (Konishi et al, 2004;Zhang et al, 2014). It has been reported that the maximum concentration (C max ) of gallic acid in human plasma following oral administration of 50 mg galic acid was about 0.3 mg/L (Shahrzad & Bitsch, 1998).…”
Section: Discussionmentioning
confidence: 99%